Analysis of The Level of Physical Fitness of Male Students In Extracurricular Volleyball Games at SMK Koperasi Pontianak - Maksum, Henry; Rahmat, Ade (COMPETITOR: Jurnal Pendidikan Kepelatihan Olahraga, 2025)
The purpose of this study was to determine the level of BMI/body mass index, muscle endurance level, muscle strength level, speed level, and cardiovascular endurance level in volleyball extracurricular students at SMK Koperasi Pontianak. This study used quantitative descriptive research. Used in this study is descriptive statistics with presentation in the form of percentages. The population and sample of this study were male participants of volleyball extracurricular activities at SMK Koperasi Pontianak, with a total of 20 students. The research sample was conducted using the total sampling technique. The data collection technique in this study used a test and measurement instrument consisting of five items, namely Body Mass Index (BMI), v sit and rich test, sit up test, squat thrust test, and PACER test..  BMI test research is 90% (18 students) in good classification. V sit and rich test 75% (15 students) in good classification, sit up test 80% (16 students) in good classification, squat thrust test 60% (12 students) in good classification, PACER test 55% (11 students) in sufficient classification. Calculation of the average value of the v sit and rich test 3.75, sit up test 4.0, squat thrust test 4.4, PACER test 3.45 and BMI 1.12. Calculation of the overall average value is 3.34. So it can be concluded that the average physical fitness of male students in extracurricular volleyball at SMK Koperasi Pontianak is in good classification, Based on the results of research conducted on male students participating in extracurricular volleyball at SMK Koperasi Pontianak, it can be concluded that their general physical fitness level is in the category according to the results: good/sufficient/less. This can be seen from the results of physical fitness tests that include components of muscle strength, endurance, speed, agility, and cardiorespiratory endurance. Factors that influence the level of fitness include the intensity of extracurricular training, lifestyle, and active participation of students in physical activities outside of school. These findings indicate the importance of implementing a structured and sustainable training program to improve the quality of students' physical fitness, especially for those who are active in sports activities such as volleyball.